PERCEIVED BENEFIT CHANGE TO SELF-SCREENING BREAST CANCER DISEASES AMONG YOUNG MOTHER WITH HEALTH BELIEF MODEL APPROACH (Proceedings of the International Conference on Public Health, 2017)
Background : Breast cancer is one of the main causes of death that resulted by cancer in women. Self-screening breast cancer a significant action to decrease mortality among young mother form breast cancer diseases. Primary prevention breast cancer disases include: mammografy, clinical breast examination, and self-screning. The purpose of this study is to analys a perceived benefit change to self-screening breast cancer disease among young mother with Health Belief Model approach. Research Method: Design this study is quasi-experiment one group pretest-posttest approach. This experiment during one week on June 2016. The subject of this experiment were 60 woman by using Purposive Sampling. The data analyzed by computerize system by SPSS version 20 by wilcoxon and significant level was 0,05. Result : The result analysis was p = 0,000 and then p
Keywords: Perceived benefit, young mother, self-sreening